A qualitative exploration on use of long acting reversible contraceptives among married women at Mzimba South District Hospital - Phethi, Chisomo (2021)
Long acting reversible contraceptives (LARC) are safe, cost-effective, and highly effective in the prevention of unplanned pregnancies for almost all women in the reproductive age group. Nationally, most married women 30% (4839) use Depo Provera with a high discontinuation rate of 41%, while 12% (1936) use Implants and 1 % (161) IUD, with a discontinuation rate of 8% for both. Records at Mzimba South District Hospital for the 2016-2017 fiscal year on the use of Implants and IUD among married women remains very low. Literature on quantitative studies indicates lack of knowledge, dependence on a provider for information, partner disapproval, myths, and misconceptions as some of the underlying factors to low uptake of Implants and IUD and yet did not capture detailed reasons as to why married women do not use Implants and IUD. The aim was to explore factors influencing the use of LARC among married women at Mzimba South District Hospital and a descriptive exploratory qualitative design was used. A purposive sample of 10 married couples was used. Data were analysed manually using thematic content analysis. The study findings generated 5 themes: inadequate knowledge of married women and their partners on Implants and IUD, source of information about Implants and IUD, reasons for partner approval/disapproval to use of Implants and IUD, reasons why married women do not use Implants and IUD for family planning, myths, and misconceptions among couples on use of Implants and IUD, perceptions of couples on use of Implants and IUD. Several factors influenced the use of Implants and IUD such as inadequate knowledge, myths and misconceptions, men’s approval, cultural beliefs, provider bias, health problems and side effects. Comprehensive contraceptive counselling on LARC is essential in knowledge acquisition hence promote LARC uptake among couples at the facility level.